Perlindungan Hukum Bagi Korban Penipuan Jual Beli Online - Anggreany Haryani Putri; Endang Hadrian (KRTHA BHAYANGKARA, 2022)
The development of an increasingly modern era, along with the growth of buying and selling transactions where this transaction activity develops following technological advances. Buying and selling transactions that were initially done with conventional methods developed in an online direction. The rapid development of buying and selling transactions must also be balanced by the rule of law to protect online buying and selling transactions, so, law No. 19 of 2016 on changes to Law No. 11 of 2008 on Information and Electronic Transactions. But even though the rules governing criminal acts still occur often, one of them is fraud in buying and selling online. This criminal act of online buying and selling fraud in its settlement refers to the provisions of Article 378 of the Criminal Code on Fraud because in article 28 paragraph 1 of the ITE Law does not regulate strictly regarding online fraud acts. The form of legal protection against victims of online fraud has not been expressly regulated in existing legislation, such as granting victims' rights in the form of compensation.